The Impact of Network Relationships on Smes' Internationalization Process: A Case Study of Malaysian Firms - Ng, Siew Imm (2002)
Today most business activities are global in scope. A firm that fails to make a global profit may well go out of business. Therefore, more and more Malaysian firms are striving to have an international presence. But when firms decided to explore international market, they begin to face a lot of challenges that require them to take strategic decisions. Therefore, this study intended to look into bow indigenous software firms use their network relationships to facilitate their internationalization process. This research used a multi-site case study methodology to more effectively identify and understand detailed international growth patterns and processes. Three respondent software finns were randomly selected from MSC (Multimedia Super Corridor) status SMEs (Small Medium-sized Enterprises). On top of that, a manufacturing firm was conveniently selected to compare differences on network relationships' influence on its internationalization process with those of manufacturing firms. In each case, upper level managers were interviewed. Information was also collected from printed documents or Internet to increase source validity. In summary, the evidences from the three software firms were found to support the firms' internationalization process in the following: • Network relationships trigger international opportunity. • Network relationships motivate firms to internationalize. • Network relationships influence firms' market selection decision. • Network relationships influence firms' entry mode decision. • Network relationships allow firms' to access additional relationships. • Network relationships allow firms' to access established channel. • Network relationships help lower cost and minimize risk. • Network relationships influence firms' internationalization pace and pattern. Therefore, managers need to have a better understanding of the impact of network relationships on firms' internationalization process as it facilitates their internationalization process through the above. A limitation of this study is that it focused on a single sector, software development firm, with only a manufacturing firm taken for comparison. It would be inappropriate to generalize the results too widely. Although case research provides a richness and depth of understanding, to enhance the qualitative approach, it is suggested that a quantitative research is adopted in future research to enhance or further reinforce the findings.